Assistência e aprendizado em Artemídia: relato de monitoria em 2017 no Instituto de Artes - Hanazumi, Paulo Yoshio Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This term paper proposes itself to narrate, and briefly analyze, the context and the situations that shaped the class assisting and monitoring period of the Media 5 classes in the Institute of Arts (Instituto de Artes, IA) of UNESP in the year 2017, with some commentary on the assisting activities of other Media disciplines taught at the IA between 2017 and 2019. The text will address the conditions that lead to the formation of the assistant and monitor team relevant to the narration, the obstacles tackled in providing assistance and monitoring throughout Media 5 classes in 2017, and the ideas and methodology developed in order to follow through this process, reflecting over the choices made and their respective results. Written entirely in Portuguese (PT-BR).

Este Trabalho de Conclusão se propõe a relatar e, de forma breve, analisar o contexto e as situações que caracterizaram o período de monitoria de aulas de Mídia 5, no Instituto de Artes (IA) da UNESP em 2017, com comentários sobre a monitoria em outras matérias de Mídia no Instituto de Artes, no período entre 2017 e 2019. O texto tratará das condições que culminaram na formação da equipe de monitoria relevante ao relato, os obstáculos encontrados na monitoria de Mídia 5 em 2017, e as ideias e metodologia criada para percorrer o trajeto da monitoria, refletindo sobre as escolhas feitas e os resultados respectivos.
Assistance and attainment in Artemídia: description of academic monitoring in the Intittute of Arts, 2017
Keywords: Art; Art and technology; Personal narratives; Arte; Mídia digital; Programas de estágios; Narrativas pessoais